Multiple Sclerosis Relapses Following Cessation of Fingolimod - Malpas, Charles B; Roos, Izanne; Sharmin, Sifat; Buzzard, Katherine; Skibina, Olga; Butzkueven, Helmut; Kappos, Ludwig; Patti, Francesco; Alroughani, Raed; Horakova, Dana; Havrdova, Eva Kubala; Izquierdo, Guillermo; et al. (Clinical drug investigation, 2022)
BACKGROUND: There is growing interest in the issue of disease reactivation in multiple sclerosis following fingolimod cessation. Relatively little is known about modifiers of the risk of post-cessation relapse, including the delay to commencement of new therapy and prior disease activity. OBJECTIVE: We aimed to determine the rate of relapse following cessation of fingolimod and to identify predictors of relapse following cessation. METHODS: Data were extracted from the MSBase registry in March 2019. Inclusion criteria were (a) clinically definite relapsing multiple sclerosis, (b) treatment with fingolimod for ≥ 12 months, (c) follow-up after cessation for ≥ 12 months, and (d) at least one Expanded Disability Status Scale score recorded in the 12 months before cessation. RESULTS: A total of 685 patients were identified who met criteria. The mean annualised relapse rate was 1.71 (95% CI 1.59, 1.85) in the year prior to fingolimod, 0.50 (95% CI 0.44, 0.55) on fingolimod and 0.43 (95% CI 0.38, 0.49) after fingolimod. Of these, 218 (32%) patients experienced a relapse in the first 12 months. Predictors of a higher relapse rate in the first year were: younger age at fingolimod cessation, higher relapse rate in the year prior to cessation, delaying commencement of new therapy and switching to low-efficacy therapy. CONCLUSIONS: Disease reactivation following fingolimod cessation is more common in younger patients, those with greater disease activity prior to cessation and in those who switch to a low-efficacy therapy.
Keywords: Multiple Sclerosis, Relapsing-Remitting; Multiple Sclerosis; relabující-remitující roztroušená skleróza; Immunosuppressive Agents; Fingolimod Hydrochloride; fingolimod hydrochlorid; imunosupresiva; Humans; Recurrence; recidiva; roztroušená skleróza; lidé